ORTHOGONAL COMPONENTS OF THE THREE-PHASE CURRENT AT ASYMMETRICAL ACTIVE-REACTIVE LOAD IN 4-WIRE CIRCUIT - Iu.A. Sirotin (National Technical University "Kharkiv Polytechnic Institute", 2016)
Purpose. For the unbalanced sinusoidal mode with asymmetric voltage in 3-phase 4-wire to receive the orthogonal 4-component decomposition of 3-phase current, are classified symmetry/asymmetry of active and reactive load elements separately. Methodology. The methodology is based on the vector approach, which with one voice allows to analyze the energy characteristics of a 4-wire and 3-wire circuits as balanced and unbalanced modes. At asymmetrical voltage the matrix representation methodology of the equivalent conductivities is used. Results. For 3-phase 4-wire network with a sinusoidal unbalanced mode with asymmetric voltage obtained 4-component orthogonal decomposition of the 3-phase current. The components have a clear electro-energetic sense and are classified irrespective by the load condition. Originality. The resulting decomposition current develops the theory Currents' Physical Components (CPC) for 4-wire circuit with asymmetric voltage. For the first time the unbalanced current is classified by activity and reactivity of asymmetry load elements. Practical value. Practical value of the obtained orthogonal decomposition current and the power equation is a possibility of their utilization for the increase both quality of delivery and quality of consumption of electrical energy.